ChemInform Abstract: One‐Pot Synthesis of 7, 9‐Dialkylpurin‐8‐one Analogues: Broad Substrate Scope. Issue 21 (27th May 2014) - Li, Jian‐Ping; Huang, Yu; Xie, Ming‐Sheng; Qu, Gui‐Rong; Niu, Hong‐Ying; Wang, Hai‐Xia; Qin, Bo‐Wen; Guo, Hai‐Ming
Abstract The title Cu‐catalyzed synthesis avoids multistep synthesis of quaternary ammonium‐salts as precursors and expands the scope of halogenated alkanes.